THE ROLE OF SCOUTING ACTIVITIES IN IMPROVING STUDENT INDEPENDENCE AND RESPONSIBILITY - Ajeng Angelia Damastitik; Adelina Hasyim; Mohammad Mona Adha (FKIP Unila, 2012)
This study aims to (1) Determine the role of scouting activities in improving the independence of students in Senior High School 1 Sumberejo, (2) Knowing the role of scouting activities in improving the independence of students in SMA Negeri 1 Sumberejo. Method used descriptive quantitative. Sample was 30 persons. Data analyses used Chi Quadrate. Research result showed that: (1) The role of scouting activities to improve students'self in Senior High School 1 Sumberejo on the calculation results of the study revealed that there is a positive and powerful category of closeness between the role of scouting activities to increase student independence. (2) The role of scouting activities to improve student responsibility performed in Senior High School 1 Sumberejo on the calculation results of the study revealed that there is a positive and powerful category of closeness between the role of scouting activities to enhance the student's responsibility. This shows that the scouting activity has a strong role in increasing independence and responsibility in class XI student of Senior High School 1 Sumberejo school year 2012/2013. Keywords: Scouts, Independence, Responsibility, Extracurricular, Builder